2015
DOI: 10.1093/icvts/ivv307
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative bronchial stump air leak control by Progel® application after pulmonary lobectomy

Abstract: Diffuse tracheobronchial calcification is a physiological condition associated with advanced age, especially in women. A calcified bronchus can be fractured during major lung resections (lobectomy, bilobectomy, and pneumonectomy), exposing patients to intraoperative air leakage and broncho-pleural fistula (BPF) occurrence. We retrospectively evaluated the use of Progel® application on the suture line of bronchial stump after pulmonary lobectomy analysing the intraoperative air leak and BPF occurrence. Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…H 2 O, Progel = 40.4 in. H 2 O) . Previously, Fenn et al investigated the effect of precursor concentration on the burst pressure properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O, Progel = 40.4 in. H 2 O) . Previously, Fenn et al investigated the effect of precursor concentration on the burst pressure properties.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, Progel (BARD) is the only surgical sealant approved specifically for pleural air leaks, composed of albumin and a polyethylene glycol-based cross-linker, applied in conjugation with sutures. Limitations of the current clinical lung sealant include the high cost of human-based albumin and elevated risk of an immune response. , Other commercially available sealants, such as cyanoacrylate-based materials (e.g., Super Glue) and fibrin tissue adhesives, are limited by inadequate mechanical strength, and the lack of degradability or biocompatibility; in addition, these sealants were not designed for use with lungs. , Therefore, the development of novel nontoxic surgical adhesives, with suitable adhesive strength and tunable mechanical properties, is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Progel combines polyethylene glycol and human serum albumin to form a hydrogel sealant that is malleable, highly adherent, and tear-resistant. In a study by Ibrahim et al involving 11 patients who suffered bronchial fractures during lung resection leading to a high risk of air leak and BPF, the application of Progel was shown to be 100% effective in preventing air leak, while no complications were identified [19]. In addition, in a study involving 2,670 patients, Mortman et al demonstrated that the use of Progel to seal air leak intraoperatively led to reduced length of stay when compared to other sealants (9.9 vs. 11.3 days; p<0.001) [20].…”
Section: Discussionmentioning
confidence: 99%
“…11–12 In fact, there is currently only one surgical sealant approved for use as a lung tissue sealant, Progel ™ (Bard-Davol), a polyethylene glycol-based product which utilizes human-derived serum albumin as a crosslinking agent. 1315 The use of human-derived products not only increases cost but can also introduce immunogenic risk factors, and thus synthetic biomaterial sealants are sought to alleviate these concerns. Approaches using fibrin or cyanoacrylate glues or other liquid sealants, applied either directly to the lung surface or instilled into the airways have not been widely successful to date and have not been pursued further for use in these applications.…”
Section: Introductionmentioning
confidence: 99%
“…Few effective means exist of patching a lung injury to effectively stop an air or fluid leak and allow appropriate healing to occur. Although one photopolymerizable sealant, FocalSeal-L (Focal, Inc.), was previously investigated, showing some success and gaining FDA approval in 2000, this product ultimately failed to enter the U.S. commercial market due to poor clinical performance. , In fact, there is currently only one surgical sealant approved for use as a lung tissue sealant, Progel (Bard-Davol), a polyethylene glycol-based product which utilizes human-derived serum albumin as a cross-linking agent. The use of human-derived products not only increases cost but also can introduce immunogenic risk factors, and thus synthetic biomaterial sealants are sought to alleviate these concerns. Approaches using fibrin or cyanoacrylate glues or other liquid sealants, applied either directly to the lung surface or instilled into the airways, have not been widely successful to date and have not been pursued further for use in these applications. In addition, prolonged tissue damage due to an underlying disease, infection, or cancer has not been addressed by the current methods.…”
Section: Introductionmentioning
confidence: 99%